Detection and infectivity potential of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) environmental contamination in isolation units and quarantine facilities. (December 2020) - Ben-Shmuel, Amir; Brosh-Nissimov, Tal; Glinert, Itai; Bar-David, Elad; Sittner, Assa; Poni, Reut; Cohen, Regev; Achdout, Hagit; Tamir, Hadas; Yahalom-Ronen, Yfat; Politi, Boaz; Melamed, Sharon; et al.
Abstract: Objectives: Environmental surfaces have been suggested as likely contributors in the transmission of COVID-19. This study assessed the infectivity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contaminating surfaces and objects in two hospital isolation units and a quarantine hotel. Methods: SARS-CoV-2 virus stability and infectivity on non-porous surfaces was tested under controlled laboratory conditions. Surface and air sampling were conducted at two COVID-19 isolation units and in a quarantine hotel. Viral RNA was detected by RT-PCR and infectivity was assessed by VERO E6 CPE test. Results: In laboratory-controlled conditions, SARS-CoV-2 gradually lost its infectivity completely by day 4 at ambient temperature, and the decay rate of viral viability on surfaces directly correlated with increase in temperature. Viral RNA was detected in 29/55 surface samples (52.7%) and 16/42 surface samples (38%) from the surroundings of symptomatic COVID-19 patients in isolation units of two hospitals and in a quarantine hotel for asymptomatic and very mild COVID-19 patients. None of the surface and air samples from the three sites (0/97) were found to contain infectious titres of SARS-Cov-2 on tissue culture assay. Conclusions: Despite prolonged viability of SARS-CoV-2 under laboratory-controlled conditions, uncultivable viral contamination of inanimate surfaces might suggest low feasibility for indirect fomite transmission.